Spliced-Leader RNA as a Dynamic Marker for Monitoring Viable Leishmania Parasites During and After Treatment. - Hendrickx, R.; Melkamu, R.; Tadesse, D.; Teferi, T.; Feijens, P. B.; Vleminckx, M.; van Henten, S.; Alves, F.; Shibru, T.; van Griensven, J.; Caljon, G.; Pareyn, M. (J Infect Dis, 2024)
Accurate detection of viable Leishmania parasites is critical for evaluating visceral leishmaniasis (VL) treatment response at an early timepoint. We compared the decay of kinetoplast DNA (kDNA) and spliced-leader RNA (SL-RNA) in vitro, in vivo, and in a VL patient cohort. An optimized combination of blood preservation and nucleic acid extraction improved efficiency for both targets. SL-RNA degraded more rapidly during treatment than kDNA, and correlated better with microscopic examination. SL-RNA quantitative polymerase chain reaction emerges as a superior method for dynamic monitoring of viable Leishmania parasites. It enables individualized treatment monitoring for improved prognoses and has potential as an early surrogate endpoint in clinical trials.
Keywords: Humans; *Leishmaniasis, Visceral/diagnosis/drug therapy/parasitology; *DNA, Kinetoplast/genetics; *RNA, Spliced Leader/genetics/metabolism; RNA, Protozoan/genetics/analysis; Animals; Leishmania/genetics; Antiprotozoal Agents/therapeutic use; Biomarkers